2014
DOI: 10.2217/fon.14.197
|View full text |Cite
|
Sign up to set email alerts
|

Promising New Therapies in Advanced Pancreatic Adenocarcinomas

Abstract: Pancreatic ductal adenocarcinoma is a lethal disease due to late diagnosis, early metastasis and the lack of effective therapies. In patients with metastatic disease, 1-year survival ranges from 17 to 23% and 5-year survival is less than 5%. This necessitates an urgent need for developing more effective therapies. Targeting the neoplastic cells has been largely ineffective due to the dense stroma, which is a physical barrier for effective drug delivery and also a source for different factors that promote tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Thus, our finding may provide an explanation for the ineffectiveness of single signal inhibition of the Hh and c-Met pathways (53). Controversial data have been reported on the role of Hh signaling and stromal depletion.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, our finding may provide an explanation for the ineffectiveness of single signal inhibition of the Hh and c-Met pathways (53). Controversial data have been reported on the role of Hh signaling and stromal depletion.…”
Section: Discussionmentioning
confidence: 74%
“…Most patients present with metastatic disease at diagnosis and have only a 2% five-year survival (2). To date, the rate of successful clinical trials in pancreatic cancer remains low (8). Of the many therapies investigated in large clinical trials over the past two decades, only two systemic therapies have demonstrated a statistically significant and clinically meaningful improvement in overall survival (OS) as compared to gemcitabine alone (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Even when the disease is diagnosed at an early stage, the prognosis is dismal [1]. In metastatic disease, modern chemotherapy regimens such as FOLFIRINOX and nab-paclitaxel plus gemcitabine produce median survival times of less than a year [3, 4], underscoring the urgent need for novel therapies [5]. Despite many agents tested, only the EGFR tyrosine kinase inhibitor erlotinib has gained FDA approval in combination with gemcitabine [6], based on a 2-week improvement in survival compared to gemcitabine alone [7, 8].…”
Section: Introductionmentioning
confidence: 99%